Assessing hand dysfunction in cervical spondylotic myelopathy. - Zachary A Smith; Alexander J Barry; Monica Paliwal; Benjamin S Hopkins; Donald Cantrell; Yasin Dhaher (PLoS ONE, 2019)
Methods Twenty patients with CSM and 17 controls were recruited. Clinical scores of modified Japanese Orthopedic Association (mJOA) and Nurick were collected. MRI based compression grades such as cord distortion were assessed. Hand dysfunction was tested using a custom motorized apparatus. Subject's forearm was placed in a cast and positioned such that their metacarpophalangeal (MCP) joint was vertically aligned with the motor shaft. Surface electromyographic sensors were placed on flexor digitorum superficialis (FDS) and extensor digitorum communis muscles. Hyperreflexia was measured as the FDS muscle activation during reflex when the MCP joint was moved from flexion to extension at 300°/sec. Proprioception was quantified as the angle of detection in absence of visual or auditory cues (subjects were blindfolded and given noise-cancelling headphones). Strength was measured as the maximum isometric force at the MCP joint. 2-sample t-test (p<0.05) were performed to assess significant differences in reflexes, proprioception and strength among patients and controls (SPSS software version 24). Results Patients reported higher Nurick (1.90±1.0 vs 0±0, p<0.001) and lower mJOA scores (14.3±1.9 vs 18.0±0, p<0.001) as compared to controls. Similarly, patients with CSM had increased reflexes (peak FDS EMG) (0.073±0.096 vs. 0.014±0.010, p = 0.019). Patient proprioception was significantly worse; mean angle of detection was greater than twice as high in patients (9.6± 9.43°) compared to controls (4.0± 2.3°), p = 0.022. MRI based compression ratio (CR) was a significant predictor of hyperreflexia, CR<0.44 resulted in steep increase in reflex activity. Fifteen of the 20 patients who completed follow up testing at 6 months after surgery show substantial clinical improvement in reflexes and proprioceptive angle, while repeated testing in controls were unchanged. Conclusion In conclusion, hyperreflexia and decline in proprioception are the main drivers of hand disability in patients with CSM. Of multiple scales, only a select few MRI scales (such as compression ratio) were predictive of increased reflexes. The study describes a pre-clinical testing apparatus to quantitatively and objectively assess primary presenting symptoms in CSM. This pilot apparatus has the potential to evaluate treatment efficacy through repeated testing. Objective testing of hand dysfunction can help inform the design of clinically feasible devices, guide MRI biomarker analysis, and improve our understanding of the progression of neurological injury in this patient population.